Susceptibility to Coffee Staining during Enamel Remineralization Following the In-Office Bleaching Technique: An In Situ Assessment - Mori, Aline Akemi [UNESP]; Lima, Fernanda Ferruzzi [UNESP]; Benetti, Ana Raquel; Suga Terada, Raquel Sano; Fujimaki, Mitsue; Pascotto, Renata Correa (Wiley-Blackwell, 2016)
Purpose: To assess in situ the enamel mineralization level and susceptibility to coffee staining after in-office bleaching. Materials and Methods: Thirty-six human dental fragments assembled into intraoral devices were bleached with 35% hydrogen peroxide and treated as follows: (group 1) no contact with coffee; (group 2) immersion in a coffee solution for 30 minutes daily for 7 days, starting 1 week after bleaching; and (group 3) immersion in a coffee solution for 30 minutes daily for 14 days, starting immediately after bleaching. Enamel mineralization and color were assessed before bleaching (T1), immediately after bleaching (T2), and after 7 (T3) and 14 days (T4). The CIE whiteness index (W*) and closeness to white (Delta W*) following bleaching and/or immersion in coffee were calculated. Data were analyzed with Friedman and Wilcoxon tests or Kruskal-Wallis and Mann-Whitney U-tests (alpha=0.05). Results: Significant differences in the mineralization levels were observed as a function of time. No significant differences in W* were observed between groups, nor was W* significantly different at T3 and T4. Similar Delta W* was observed between groups after 7 or 14 days. Conclusions: The mineral loss after in-office bleaching was progressively reversed by contact with saliva for 14 days. The whiteness index was not affected by contact with coffee during the remineralization period. CLINICAL SIGNIFICANCE The results of this in situ study suggest that the mineral loss caused by in-office dental bleaching is minimal and is partly compensated by remineralization due to contact with saliva. Additionally, whiteness was not affected by daily exposition to coffee during the enamel remineralization, which indicates that avoiding the consumption of coffee immediately following in-office bleaching is unnecessary.